2005
DOI: 10.1093/brain/awh546
|View full text |Cite
|
Sign up to set email alerts
|

Megadolichobasilar anomaly with thrombosis in a family with Fabry's disease and a novel mutation in the α-galactosidase A gene

Abstract: Fabry's disease is an X-linked lysosomal storage disorder. alpha-Galactosidase deficiency leads to accumulation of globotriaosylceramide mainly in endothelial and smooth muscle cells. Cerebrovascular symptoms with predominant affection of the vertebrobasilar circulation are one of the major sources of morbidity in Fabry's disease. We present a Hungarian family with Fabry's disease caused by a new mutation in the alpha-galactosidase A gene (GLA), and describe a variant expression of the disease. Megadolichobasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…[9][10][11][12][13] A few studies applied a semiquantitative or quantitative approach with MRA 3D reconstructions (2 studies with 1.5T and 1 with 3T scanner), [14][15][16]19 T2 axial images (van der Tol L, personal communication), either T2 axial images or MRA, 17 or axial partitions of MRA (present study). Despite different methods, sequences, and scanners used for the measurement and the different ways to present study findings (different patient subgrouping, mean or median value, etc), all studies consistently showed the increase of the basilar artery diameter in patients with FD compared with control patients (On-line Table 2).…”
Section: Basilar Artery Diameter Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] A few studies applied a semiquantitative or quantitative approach with MRA 3D reconstructions (2 studies with 1.5T and 1 with 3T scanner), [14][15][16]19 T2 axial images (van der Tol L, personal communication), either T2 axial images or MRA, 17 or axial partitions of MRA (present study). Despite different methods, sequences, and scanners used for the measurement and the different ways to present study findings (different patient subgrouping, mean or median value, etc), all studies consistently showed the increase of the basilar artery diameter in patients with FD compared with control patients (On-line Table 2).…”
Section: Basilar Artery Diameter Changesmentioning
confidence: 99%
“…[3][4][5] Increased vessel tortuosity has been found in the retina 6 and in the skin, 7,8 and intracranial artery dolichoectatic changes have been repeatedly observed in patients with FD during both pathologic and neuroimaging evaluations. [9][10][11][12][13][14][15][16][17] Hitherto, most of the latter studies either referred to small samples or evaluated single specific aspects of artery dolichoectasia (such as the vessel lumen diameter). In addition, these studies applied different quantification methods or semiquantitative scores for the severity of the intracranial FD-related vessel changes, leading to conflicting results about the role of sex, age, and treatments.…”
mentioning
confidence: 99%
“…These include extensive white matter changes, 4,5 cerebral infarctions especially in regions supplied by the posterior circulation, 6,7 and associated dilatation of the vertebrobasilar vessels 6,7 up to extensive dolichoectasia. 8 In addition, although such abnormalities can have several causes, the observation of high signal intensity of the pulvinar thalami on T1-weighted magnetic resonance imaging (MRI) in up to one quarter of individuals diagnosed with FD was suggested to be pathognomonic of this disorder. 9,10 The Stroke in Young Fabry Patients (SIFAP 1) study prospectively investigated an unselected study population of young patients with an acute cerebrovascular event (CVE) and found a proportion of 0.9% to have definite or probable FD using genetic testing and determination of globotriaosylceramide in blood and urine and of lyso-globotriaosylceramide in human plasma.…”
mentioning
confidence: 99%
“…More than 200 mutations distributed over the entire a-Gal A gene have been reported, and they include all types of gene defects (Pastores and Lien, 2002;Schafer et al, 2005). Most of the mutations have been found in single families (Garzuly et al, 2005;Sorensen, 2002). The deficit of a-Gal A enzyme is responsible for the accumulation of glycosphingolipids, particularly globotriaosylceramide, within the heart, kidney, brain, peripheral nerves, eyes, skin, and vascular tissues.…”
Section: Genetic and Pathological Aspectsmentioning
confidence: 99%
“…Globotriaosylceramide is stored particularly in the vascular smooth muscle and endothelial cells with cell dysfunction and development of tissue ischemia and infarction. The deposition of globotriaosylceramide was documented within the cerebral vascular wall causing narrowing of perforating small arterioles and dolichoectasia of the large basilar and vertebral arteries (Garzuly et al, 2005). Garzuly et al (2005) described a family with megadolichobasilar and thrombosis occurring in five men and a woman caused by a mutation (c.47T-> C missense mutation) in a-Gal A gene.…”
Section: Genetic and Pathological Aspectsmentioning
confidence: 99%